PENGARUH AKTIVASI FISIKA ARANG KAYU LABAN TERHADAP EFEKTIVITAS PEMURNIAN BIOGAS & UNJUK KERJA MESIN GENERATOR-SET - Muhammad Mu’ammar; Abdul Ghofur (Scientific Journal of Mechanical Engineering Kinematika, 2016)
This study aims to determine the effect of the use of laban charcoal on the effectiveness of biogas purification & Performance Generator-Set. This research is conducted by biogas flowing from Sanitary Landfill to biogas purification insulator containing adsorption media in the form of charcoal which has been activated physics with temperature variation of 550oC, 650oC and 750oC with 1 hour time, then biogas is stored in storage tube and then tested with biogas to Chamber for the reading of carbon dioxide and methane levels using Gas Analyzer. The result of carbon dioxide 2808,61 ppm and methane 40,51 ppm without purification after purified by using the best adsorption media of laban charcoal was found at 750oC carbon dioxide 2026,55 ppm and methane 53,94 ppm with effectiveness 27,84 %. The highest biogas purification effectiveness is at 750oC. The generator-set test with biogas fuel that has been purified charcoal is activated with a temperature of 750oC. Then it is fed to the storage tube and distributed to the generator-set, taking the data of rotation, temperature, and voltage of each load, the load 0 W, 4445.9 rpm rotation, 113,4oC, and 240 V (Stable), 350 W, 2344,43 rpm, 118,36oC, 150-240 V (Not Stable), 650 W, 2185,26 rpm, 136,73oC, 100-200 V (Not Stable).